The World with an Admixture of Microplastics - Stołpiec, Katarzyna; Nowak, Bożena; Babczyńska, Agnieszka (No Limits, 2021)
Currently, plastic is the most popular synthetic product. Although its history is rather short – the first plastic was created in the mid-19th century – its versatility has resulted in massive production around the world. The process of disposing of plastic-derived waste does not keep up with its grinding, and therefore the amount of synthetic waste grows at an increasing pace. By means of their inventions, environmentalists hope to move the consciences of consumers who buy food in plastic packaging, guided rather by their own convenience than care for the environment. How many of them actually know how dangerous the plastic they buy can be?